GAME-FACILITATED DEVELOPMENT OF INTERCULTURAL COMMUNICATIVE COMPETENCE IN BASIC SCHOOL STUDENTS - Aknur Amangeldina; Zhumabekova Galiya Baiskanova (Foundations and Trends in Modern Learning, 2025)
Intercultural communicative competence (ICC) has become a core priority in basic school education due to the increasing cultural diversity of contemporary classrooms and the demands of global citizenship. Traditional instructional approaches often fail to provide meaningful and engaging intercultural experiences for young learners. This study investigates the effectiveness of game-facilitated learning strategies for developing ICC among basic school students. Drawing on gamification principles, a series of game-based intercultural tasks were designed and implemented in English classes for learners aged 11–13. A mixed-method design was employed, including pre- and post-intervention ICC assessments, classroom observations, student surveys, and teacher interviews. Quantitative data indicate statistically significant improvements in students’ intercultural attitudes, cultural awareness, empathy, and communicative strategies. Qualitative findings reveal heightened motivation, reduced anxiety in cross-cultural communication, and increased collaborative behavior. Students demonstrated higher engagement when tasks involved role-playing, simulation games, storytelling challenges, and problem-solving missions embedded in culturally diverse contexts. This study contributes empirical evidence and a practical pedagogical framework for integrating game-based learning into ICC development at the basic school level. It highlights the potential of interactive, narrative-rich, and emotionally engaging game tasks to cultivate curiosity, respect for cultural differences, and communicative flexibility among young learners